2022
DOI: 10.1111/pan.14617
|View full text |Cite
|
Sign up to set email alerts
|

Childhood obesity trends: Association with same‐day hospital admission in a National Outpatient Surgical Population

Abstract: Background Although the prevalence of obesity in the general population and its perioperative implications among children undergoing inpatient surgeries are well known, little is known about obesity prevalence among children scheduled for ambulatory surgery. Aims Here, we report the trends of obesity and severe obesity among children who underwent ambulatory surgery across multiple centers in the United States and explore the association of obesity status with admission following elective ambulatory surgery. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
(31 reference statements)
0
2
0
Order By: Relevance
“…Obesity increases perioperative respiratory adverse events [7 ▪ ,19] as well as the likelihood of unanticipated admission [7 ▪ ,22 ▪▪ ]. A recent study of the National Surgical Quality Improvement Program-Pediatric (NSQIP-P) database by Tram et al [22 ▪▪ ] found higher rates of same day hospital admission following elective ambulatory surgery in children with severe (Class 2/3) obesity compared to healthy weight children. This finding is even more striking in light of the fact that NSQIP-P does not collect data on routine tonsillectomies, or any data from freestanding ASCs.…”
Section: Obesitymentioning
confidence: 99%
“…Obesity increases perioperative respiratory adverse events [7 ▪ ,19] as well as the likelihood of unanticipated admission [7 ▪ ,22 ▪▪ ]. A recent study of the National Surgical Quality Improvement Program-Pediatric (NSQIP-P) database by Tram et al [22 ▪▪ ] found higher rates of same day hospital admission following elective ambulatory surgery in children with severe (Class 2/3) obesity compared to healthy weight children. This finding is even more striking in light of the fact that NSQIP-P does not collect data on routine tonsillectomies, or any data from freestanding ASCs.…”
Section: Obesitymentioning
confidence: 99%
“…624-629) provide a detailed description of expanded measures of quality and outcomes in ambulatory surgery with a discussion of patient reported outcome measures and value-based care. Pediatric patients undergoing ambulatory surgery were long considered ''healthy'' but that is no longer true given the increasing prevalence of obesity and associated comorbidities in this population [7]. Weber et al (pp.…”
mentioning
confidence: 99%